Development of enterobacter-enriched alginate bead biofertilizer for phosphate and potassium acquisition to improve okra [Abelmoschus esculentus (L.) Moench] growth and productivity - Mohamad Roslan, Muhamad Aidilfitri (2022)
Microbial biofertilizer application has been recognized as a sustainable alternative to synthetic fertilizers for the past two decades. The core ingredient in this technology i.e., plant-growth-promoting (PGP) bacteria exerts a broad functional tool for the enrichment of soil fertility. This will help elevate plantavailable macronutrient deficiency in soil like phosphate (P) and potassium (K) which is prevalent in many agricultural fields. Deficiency in soil available P and K often hinder optimum growth and productivity in plants. Several issues regarding biofertilizer, such as biocompatibility of formulation and efficient delivery into soil systems, remain a challenge. The general objectives of the present study were to screen for the best candidate of P- and K-solubilizing bacteria, to investigate the effects of seed biopriming on okra seedlings, to formulate a sustainable medium and carrier in maintaining an optimal shelf life of bacteria and eventually evaluate the effects of bacterial inoculation in soil on the growth and yield performance of okra in greenhouse conditions. Out of eighteen isolates, Enterobacter cloacae 38, Enterobacter hormaechei 15a1 and 40a demonstrated the highest P- and K-solubilizing activities while demonstrating additional PGP potentials such as nitrogen fixation, exopolysaccharide, indole-3-acetic acid, and siderophore production. The okra seed germination assay revealed that all of the Enterobacter spp. significantly improved seedling vigor index (19.6%) and exhibited root colonization competence. The bioprimed okra seedlings in the pot experiment showed significant improvement of the plant growth (> 28%), the leaf surface area (> 29%), and the SPAD chlorophyll index (> 9%) which corresponded to the increase of P (> 41%) and K uptakes (> 89%) as compared to the uninoculated control. Strain 40a was selected and further evaluated in a biofertilizer formulation using molasses and defatted soybean meal (DSM). Through the twolevel factorial design and central composite design, the optimal formulation and fermentation conditions to achieve maximum cell density of strain 40a were achieved. The highest cell density of strain 40a in the optimized molasses-DSM (OMD) medium was 12.56 log CFU/mL after 24 h which was 99.7% accuracy towards the predicted value. This formulation was then improvised in the next experiment using the hydrolysate cocktail of DSM and jackfruit peel through the optimized microwave-alkaline hydrolysis to produce an Enterobacter-enriched molasses alginate bead. Results show that the P and K solubilization capacity by the encapsulated strain 40a was remarkably maintained and comparable to the free cell counterpart. The performance of both free-cell and encapsulated strain 40a was evaluated on okra plants under greenhouse conditions for 60 days. The treatments given were: Half-dose PK-fertilizer, 3H; half-dose PKfertilizer and free-cell strain 40a, 3HI; half-dose PK-fertilizer and encapsulated strain 40a, 3HB; full-dose PK-fertilizer, 3F. The results revealed that 3HB had the highest soil available P (SAP) and K (SAK), as well as P and K uptake for all plant organs, followed by 3F, 3HI, and 3H, and improved yield by up to 75.6%. We discovered increased bacterial richness and diversity in both 3HB and 3HI samples compared to uninoculated treatments. Both 3HB and 3F treatments were positively correlated with increasing abundance of Acidobacteriales, Burkholderia caballeronia paraburkholderia, Gemmataceae, and Sphingomonas as well as SAP and SAK. The effect of one-time 3HB treatment on okra growth and yield was comparable to biweekly inoculation in 3HI, suggesting a new costeffective farming approach in precision agriculture.